A review of microsatellite markers and their application on genetic diversity studies in parrots - Presti, Flávia Torres [UNESP]; Wasko, Adriane Pinto [UNESP] (Scientific Research Publishing, 2014)
The ability of a population to adapt to a changing environment depends on its genetic variation. Thus, the study of genetic diversity within and among species or populations is especially important on conservation biology scopes. One way to assess the genetic diversity is through the use of microsatellite molecular markers. Microsatellites have been widely used to answer population genetics issues as gene flow, parentage, and population structure, mostly resulting in data on the distribution of genetic variability within and among natural populations, which are essential for ex situ and in situ conservation procedures. As the Psittacidae family comprehends one of the birds group with the largest number of endangered species, studies that aim to investigate the genetic diversity of these animals may support their conservation. This article is a review of genetic data on parrots, through the use of microsatellite markers, that have been published since 2004.
Keywords: Genetic diversity; Microsatellite; Parrots